Algal biohydrogen production: Impact of biodiversity and nanomaterials induction - Singh T.; Sehgal A.; Singh R.; Sharma S.; Pal D.B.; Tashkandi H.M.; Raddadi R.; Harakeh S.; Haque S.; Srivastava M.; Aly Hassan A.; Srivastava N.; Gupta V.K. (My University, 2025)
Fossil fuels are limited in nature and are not environmentally friendly, thus using them to meet the rising energy needs is insufficient. Another major cause of global warming, which is recognized as one of the greatest hazards to the world, is fossil fuels. Finding alternative energy sources that can counteract the drawbacks of fossil fuels is urgently needed. Due to its low environmental impact and a variety of possible sustainable production methods, biohydrogen is one such alternative energy source that has attracted enormous interest and demand. Due to their wide range of environments, rapid growth, and polyphyletic nature, algae-based biological hydrogen production techniques are gaining significant interest. Nevertheless, the main obstacles to the sustainable and commercial application of the algal biohydrogen generation process are low yield, constrained light penetration, low biomass concentration, and expensive downstream processes. Increased attention to algal diversity may help to overcome the limitation of low algal biomass production and yield while enhancing penetration ability. Additionally, the usage of nanomaterials may speed up the process by altering the entire process' response mechanism. Therefore, this review explores algal diversity as one of the strategies of algal biohydrogen production along with elaboration of the impacts of nanomaterials in different pathways of biohydrogen production, namely dark fermentation, photo-fermentation, direct and indirect biophotolysis. Advances in biohydrogen production employing diversified groups of algae with the application of nanomaterials have been extensively summarized with current update mechanisms and existing roadblocks. As a result, the utilization of nanomaterials as a novel and sustainable catalyst has also been thoroughly described for prospective scaling up of algal biohydrogen production. © 2023 Elsevier Ltd